Sugarcane-based biological polyethylene degradable modified particles and preparation method thereof

By using fillers such as zinc oxide, graphite phase carbon nitride and algae powder in sugarcane-based biopolyethylene, combined with modifier treatment, the problem of poor synergy of mechanical strength and degradability of sugarcane-based biopolyethylene is solved. The coordinated improvement of high intensity and high degradation effects has been achieved.

CN119320525AInactive Publication Date: 2025-01-17QUANZHOU BINQI ENERGY TECH CO LTD

Patent Information

Application Number
CN202411874479.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Sugarcane-based biopolyethylene has poor synergy in terms of mechanical strength and degradability, and conventional improvement methods can easily affect its degradation effect.

Method used

Zinc oxide, graphite phase carbon nitride, iron oxide or nanosilver particles are used as fillers to promote polyethylene segment breakage through covalent bonding and photocatalytic activity, combining Rainbow Chlorella powder, Spirulina powder, Poria powder and tea leaves Materials such as extracts improve mechanical strength and degradation effects, and improve the dispersion and compatibility of fillers through modifier treatment.

Benefits of technology

It significantly improves the mechanical strength and degradation effect of sugarcane-based biopolyethylene, extends the service life, and maintains good environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of polyethylene, and particularly discloses sugarcane-based biological polyethylene degradable modified particles and a preparation method thereof. The sugarcane-based biological polyethylene degradable modified particle comprises the following materials in parts by weight: 100 parts of sugarcane-based polyethylene; 10 to 30 parts of filler; 2-5 parts of a lubricant; 0.5 to 2 parts of a compatibilizer; 2-5 parts of a plasticizer; the filler comprises any one or more of zinc oxide, graphite-phase carbon nitride, iron oxide and nano-silver particles. The preparation method comprises the following steps: S1, preparing raw materials; s2, preparing modified particles. The modified particles can be used in the fields of medicine and health, packaging materials, catering services, cosmetic packaging materials and the like, and have the advantages of degradability, environmental protection, high strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyester fibers, and more specifically, to a kind of sugarcane-based bio-polyethylene degradable modified particles and a preparation method thereof. Background Art

[0002] Sugarcane-based polyethylene is a type of polyethylene produced from sugarcane. Sugarcane-based polyethylene is environmentally friendly and, as a biopolymer made from natural and biodegradable raw materials, contributes to environmental protection and sustainable development. Sugarcane-based polyethylene can be widely used in medicine and health, food packaging film, automobiles, catering services, cosmetics and other fields, showing its diverse application potential.

[0003] However, the introduction of biomass materials into sugarcane-based polyethylene can easily lead to changes in the cross-linking density of polyethylene, thereby causing changes in the mechanical strength of polyethylene. The conventional method of improving the mechanical strength of polyethylene by adding fillers can easily affect the degradation effect of polyethylene. Therefore, how to make sugarcane-based bio-polyethylene synergistically achieve high strength and high degradation effect is an urgent problem that needs to be solved. Summary of the invention

[0004] In order to improve the defects of sugarcane-based bio-polyethylene in terms of strength and poor degradability synergy, the present application provides a sugarcane-based bio-polyethylene degradable modified particle and a preparation method thereof, using the following technical solution: In a first aspect, the present application provides a sugarcane-based bio-polyethylene degradable modified particle, comprising the following materials in parts by weight: 100 parts of sugarcane-based polyethylene; 10-30 parts of filler; 2-5 parts of lubricant; Compatibilizer 0.5-2 parts; 2-5 parts of plasticizer; The filler includes any one or more of zinc oxide, graphite carbon nitride, iron oxide and nano silver particles.

[0005] By adopting the above technical scheme, it is preferred to use any one or more of zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles as fillers. First, zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles can be combined with sugarcane-based polyethylene through covalent bonds, which can effectively inhibit the movement of polyethylene segments, thereby effectively improving the mechanical strength of the modified particles. Secondly, zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles all have photocatalytic activity, which can catalyze the generation of hydroxyl radicals, generate oxygen vacancies, and form active oxygen, which is conducive to promoting the breakage of CC bonds on polyethylene segments to form alkyl radicals. The alkyl radicals continue to break or continue to react with hydroxyl radicals to generate alkoxy groups, that is, to promote the degradation of sugarcane-based bio-polyethylene. Therefore, the preferred type of filler in this application can synergistically improve the mechanical strength and degradation effect of sugarcane-based bio-polyethylene, and further improve the use effect and environmental performance of sugarcane-based bio-polyethylene.

[0006] Optionally, the filler is a filler modified with a modifier, and the modifier is selected from sodium poly(p-styrene sulfonate) or methacryloxypropyltrimethoxysilane.

[0007] By adopting the above technical scheme, the filler is modified with sodium poly(p-styrene sulfonate), electrolyte particles are wrapped on the surface of the filler, and the mutual repulsion between like charges is utilized to inhibit the agglomeration of filler ions due to high surface energy, thereby effectively improving the dispersion effect of the filler in polyethylene, so that the filler can evenly improve the mechanical strength and degradation effect of polyethylene.

[0008] The filler is modified with methacryloxypropyltrimethoxysilane and grafted onto the filler through coupling, thereby reducing the surface polarity of the filler, improving the compatibility between the filler and sugarcane-based bio-polyethylene, making the filler evenly dispersed in the polyethylene, and enabling the polyethylene to obtain uniform and stable mechanical strength and degradation effect.

[0009] Optionally, the filler further comprises Haematococcus pluvialis powder or Spirulina powder.

[0010] By adopting the above technical scheme, it is preferred to use Haematococcus pluvialis powder or Spirulina powder as a filler to add to polyethylene. Since Haematococcus pluvialis powder and Spirulina powder both have more hydrophilic groups such as -OH, -C=O, and -COOH, they will be attacked by microorganisms in water, thereby giving polyethylene a better hydrophilic effect, enabling microorganisms in water to attach to the surface of the material for erosion, and the degraded algae powder can form holes and grooves in the material, which can provide more holes and grooves for microorganisms, provide more adsorption sites for microorganisms, and accelerate the breaking of covalent bonds of the composite material to achieve the purpose of accelerating the degradation of polyethylene. By coordinating Haematococcus pluvialis powder or Spirulina powder with zinc oxide, graphite phase carbon nitride, iron oxide or nano-silver particles, the degradation effect of polyethylene can be synergistically improved through photocatalytic degradation and biodegradation.

[0011] During the post-processing of polyethylene, the polyethylene is broken, thereby exposing the algae powder in the broken cross-section. The hydrophilicity of the algae powder is used to increase the loading effect and erosion effect of microorganisms on the broken polyethylene, thereby promoting the degradation of polyethylene.

[0012] Optionally, the Haematococcus pluvialis powder is Haematococcus pluvialis powder containing astaxanthin.

[0013] By adopting the above technical scheme, preferably using Haematococcus pluvialis powder containing astaxanthin as filler, polyethylene can obtain a suitable antioxidant effect, and can appropriately inhibit the degradation effect of microorganisms on polyethylene, that is, the polyethylene is not easy to degrade too quickly during use, thereby extending the service life of polyethylene.

[0014] Optionally, the filler also includes Poria cocos powder and tea extract.

[0015] By adopting the above technical scheme, preferably using Poria powder or tea extract as filler, Poria powder and tea extract both have antibacterial ingredients such as polyphenols, which can further improve the antibacterial effect of polyethylene and slow down the degradation rate of polyethylene by microorganisms, that is, the polyethylene remains stable during use and the service life of polyethylene is extended.

[0016] Optionally, the tea extract is prepared as follows: tea leaves and tea stems are crushed, immersed in ethanol, extracted at room temperature, filtered, solids are discarded, and concentrated by rotary evaporation to obtain the tea extract.

[0017] By adopting the above technical solution, the tea extraction method is optimized. After extraction by the above method, the tea extract contains a large amount of tannic acid and tea polyphenols, which give the tea extract a higher antibacterial effect.

[0018] Optionally, the tea extract is pre-dispersed in a DMSO solution with zinc oxide, iron oxide, graphite carbon nitride and nano silver ions.

[0019] By adopting the above technical scheme, tea extract, zinc oxide, iron oxide, graphite phase carbon nitride and nano silver ions are pre-dispersed in a DMSO solution. The tannic acid in the tea extract can form a complex with the metal ions, further improving the bonding effect between the filler and the polyethylene, so that the filler can stably improve the mechanical strength of the polyethylene.

[0020] Optionally, the filler further comprises orange peel powder and silicon dioxide.

[0021] By adopting the above technical solution, orange peel powder contains a large number of active functional groups such as hydroxyl and carbonyl, which can be added to polyethylene to improve the cross-linking degree of polyethylene through functional group bonding, that is, further improve the mechanical strength of polyethylene. Preferably, silicon dioxide is used as a filler and added to polyethylene. Silicon dioxide can form a strong covalent bond with the polyethylene matrix, further improving the cross-linking effect of polyethylene to improve the mechanical strength of polyethylene.

[0022] Optionally, the compatibilizer is selected from maleic anhydride grafted polyethylene with a grafting rate of 8%, the lubricant is selected from polyethylene wax or calcium stearate, and the plasticizer is glycerol.

[0023] By adopting the above technical solution, preferably using polyethylene wax or calcium stearate as a lubricant, the filler can be fully wetted and the dispersion uniformity of the filler in the polyethylene can be improved.

[0024] In a second aspect, the present application provides a method for preparing sugarcane-based bio-polyethylene degradable modified particles, comprising the following steps: S1. Raw material preparation: weigh sugarcane-based polyethylene, filler, compatibilizer, lubricant and plasticizer respectively according to the above weight parts; S2. Preparation of modified particles: The filler is crushed in advance to obtain filler powder, the filler powder is mixed with a lubricant, a bulking agent and a plasticizer in advance to obtain a mixture, and the mixture and sugarcane-based polyethylene are put into an extruder, and extruded and granulated to obtain modified particles.

[0025] In summary, this application has the following beneficial effects: 1. Since the present application preferably uses any one or more of zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles as fillers, firstly, zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles can be mutually bonded with sugarcane-based polyethylene through covalent bonds, which can effectively inhibit the movement of polyethylene segments, thereby effectively improving the mechanical strength of the modified particles. Secondly, zinc oxide, graphite carbon nitride, iron oxide or nano-silver particles all have photocatalytic activity, which can catalyze the generation of hydroxyl radicals, generate oxygen vacancies, and form active oxygen, which is conducive to promoting the breakage of CC bonds on polyethylene segments to form alkyl radicals, and the alkyl radicals continue to break or continue to react with hydroxyl radicals to generate alkoxy groups, that is, to promote the degradation of sugarcane-based bio-polyethylene. Therefore, the preferred type of filler in the present application can synergistically improve the mechanical strength and degradation effect of sugarcane-based bio-polyethylene, and further improve the use effect and environmental performance of sugarcane-based bio-polyethylene.

[0026] 2. In the present application, since both Haematococcus pluvialis powder and Spirulina powder have more hydrophilic groups such as -OH, -C=O, and -COOH, they will be attacked by microorganisms in the water, thereby giving polyethylene a better hydrophilic effect, which can make the microorganisms in the water adhere to the surface of the material for erosion, and the degraded algae powder can form holes and grooves in the material, which can provide more holes and grooves for microorganisms, provide more adsorption sites for microorganisms, and accelerate the breaking of covalent bonds of the composite material, so as to achieve the purpose of accelerating the degradation of polyethylene.

[0027] 3. In the present application, tea extract, zinc oxide, iron oxide, graphite carbon nitride and nano silver ions are pre-dispersed in a DMSO solution. The tannic acid in the tea extract can form a complex with the metal ions, further improving the bonding effect between the filler and the polyethylene, so that the filler can stabilize and improve the mechanical strength of the polyethylene. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Preparation Example Preparation Example of Tea Extract

[0030] Preparation Example 1 Tea leaves and tea stems were crushed, immersed in ethanol, extracted at room temperature for 12 hours, filtered, solids were discarded, and concentrated by rotary evaporation to obtain tea extract.

[0031] Filler Preparation Example Preparation Example 2 The filler is preferably zinc oxide, and zinc oxide and tea extract are dispersed in a DMSO solution at a mass ratio of 5:1, and filtered to obtain a premixed filler. Example

[0032] Examples 1-3 On the one hand, the present application provides a sugarcane-based bio-polyethylene degradable modified particle, including sugarcane-based polyethylene, filler, lubricant, compatibilizer and plasticizer, and the specific mass is shown in the table below.

[0033] Among them, the filler can be selected from one or more of zinc oxide, graphite phase carbon nitride, iron oxide or nano silver particles. Specifically, zinc oxide is preferably used as the filler in this embodiment. The lubricant can be selected from polyethylene wax or calcium stearate. Specifically, polyethylene wax is preferably used as the lubricant in this embodiment. The compatibilizer is selected from maleic anhydride grafted polyethylene with a grafting rate of 8% (Shanghai Yien Chemical Technology Co., Ltd.), the plasticizer is glycerol, and the sugarcane-based bio-polyethylene is a sugarcane material-polyethylene composite material, wherein the sugarcane material is sugarcane bagasse, and the sugarcane bagasse is sugarcane bagasse treated with choline chloride-urea.

[0034] On the other hand, the present application provides a method for preparing sugarcane-based bio-polyethylene degradable modified particles, comprising the following steps: S1. Raw material preparation: weigh sugarcane-based polyethylene, filler, compatibilizer, lubricant and plasticizer respectively according to the above weight parts; S2. Preparation of modified particles: The filler is crushed in advance to obtain filler powder, the filler powder is mixed with a lubricant, a bulking agent and a plasticizer in advance to obtain a mixture, and the mixture and sugarcane-based polyethylene are put into an extruder, and extruded and granulated to obtain modified particles.

[0035] Table 1 Composition of Examples 1-3

[0036] Example 4 On the one hand, the present application provides a sugarcane-based bio-polyethylene degradable modified particle, including sugarcane-based polyethylene, filler, lubricant, compatibilizer and plasticizer, and the specific mass is shown in the table below.

[0037] Among them, in this embodiment, modified zinc oxide is preferably used as the filler. The lubricant can be selected from polyethylene wax or calcium stearate. Specifically, polyethylene wax is preferably used as the lubricant in this embodiment. The compatibilizer is selected from maleic anhydride grafted polyethylene with a grafting rate of 8% (Shanghai Yien Chemical Technology Co., Ltd.), and the plasticizer is selected from glycerol.

[0038] The preparation of modified zinc oxide is as follows: Weigh 15g zinc oxide, then pour it into a 500mL container with 250mL anhydrous ethanol, and ultrasonically vibrate for half an hour. Take 1.5mL KH570, then add 50mL anhydrous ethanol and 2mL deionized water, and ultrasonically vibrate for 15 minutes. Add the hydrolyzed KH570 solution dropwise to the container containing zinc oxide, and ultrasonically vibrate for 20-30 minutes. React at 80℃ for two hours. After the reaction is complete, vacuum filter and dry the solution to obtain modified zinc oxide.

[0039] On the other hand, the present application provides a method for preparing sugarcane-based bio-polyethylene degradable modified particles, comprising the following steps: S1. Raw material preparation: weigh sugarcane-based polyethylene, filler, compatibilizer, lubricant and plasticizer respectively according to the above weight parts; S2. Preparation of modified particles: The filler is crushed in advance to obtain filler powder, the filler powder is mixed with a lubricant, a bulking agent and a plasticizer in advance to obtain a mixture, and the mixture and sugarcane-based polyethylene are put into an extruder, and extruded and granulated to obtain modified particles. Example 5

[0040] The difference from Example 4 is that the filler includes modified zinc oxide and spirulina powder in a mass ratio of 5:1 to prepare polyethylene particles. Example 6

[0041] The difference from Example 4 is that the filler includes modified zinc oxide and Haematococcus pluvialis powder containing astaxanthin in a mass ratio of 5:1 to prepare polyethylene particles. Example 7

[0042] The difference from Example 3 is that the filler includes modified zinc oxide, spirulina powder, Poria powder and tea extract in a mass ratio of 5:1:0.5:1 to prepare polyethylene particles. Example 8

[0043] The difference from Example 3 is that the filler includes modified zinc oxide, spirulina powder, Poria powder and tea extract in a mass ratio of 5:1:0.5:1, wherein the modified zinc oxide and the tea extract are premixed as in Preparation Example 2 to prepare polyethylene particles. Example 9

[0044] The difference from Example 3 is that the filler includes modified zinc oxide, spirulina powder, Poria powder, tea extract, orange peel powder and silicon dioxide in a mass ratio of 5:1:0.5:1:0.5:0.5, wherein the modified zinc oxide and tea extract are premixed as in Preparation Example 2 to prepare polyethylene particles.

[0045] Comparative Example Comparative Example 1

[0046] On the one hand, the present application provides a sugarcane-based bio-polyethylene degradable modified particle, including sugarcane-based polyethylene, filler, lubricant, compatibilizer and plasticizer, and the specific mass is shown in the table below.

[0047] Among them, silicon dioxide is preferably used as a filler in this embodiment. The lubricant can be selected from polyethylene wax or calcium stearate. Specifically, polyethylene wax is preferably used as a lubricant in this embodiment. The compatibilizer is selected from maleic anhydride grafted polyethylene with a grafting rate of 8% (Shanghai Yien Chemical Technology Co., Ltd.), and the plasticizer is selected from glycerol.

[0048] On the other hand, the present application provides a method for preparing sugarcane-based bio-polyethylene degradable modified particles, comprising the following steps: S1. Raw material preparation: weigh sugarcane-based polyethylene, filler, compatibilizer, lubricant and plasticizer respectively according to the above weight parts; S2. Preparation of modified particles: The filler is crushed in advance to obtain filler powder, the filler powder is mixed with a lubricant, a bulking agent and a plasticizer in advance to obtain a mixture, and the mixture and sugarcane-based polyethylene are put into an extruder, and extruded and granulated to obtain modified particles. Performance testing

[0049] (1) Mechanical strength: The tensile properties were tested according to GB / T1040.1-2018. The narrowest part of the spline was 9.80 mm, the thickness was 3.95 mm, the spline was dumbbell-shaped, and the tensile speed was 5 mm / min.

[0050] (2) Biodegradability analysis: The biodegradability of the modified particles was studied by aerobic (15 days) + anaerobic (15 days) degradation. The experimental period was 30 days, and the degradation rate was calculated.

[0051] (3) Antibacterial performance testing: The antibacterial activity of polyethylene against Escherichia coli (ATCC8739) was tested according to GB / T31402-2015 standard.

[0052] Table 2 Performance test

[0053] Combining the performance test comparison in Table 2, we can find that: 1. By comparing Examples 1-3 with Comparative Example 1, it can be found that the mechanical strength, degradation rate and antibacterial performance of the polyethylene prepared in Examples 1-3 are all improved, which shows that zinc oxide in the present application can be combined with sugarcane-based polyethylene through covalent bonds, which can effectively inhibit the movement of polyethylene segments, thereby effectively improving the mechanical strength of the modified particles. Secondly, zinc oxide has photocatalytic activity, which can catalyze the generation of hydroxyl radicals, generate oxygen vacancies, and form active oxygen, which is conducive to promoting the breakage of CC bonds on polyethylene segments to form alkyl radicals. Alkyl radicals continue to break or continue to react with hydroxyl radicals to form alkoxy radicals, that is, to promote the degradation of sugarcane-based bio-polyethylene, and synergistically improve the mechanical strength and degradation effect of sugarcane-based bio-polyethylene.

[0054] 2. By comparing Example 4 with Example 2, it can be found that the mechanical strength, degradation rate and antibacterial performance of the polyethylene prepared in Example 4 are all improved, which means that in the present application, methacryloxypropyltrimethoxysilane is used to modify the filler, and is grafted on the filler by coupling, thereby reducing the surface polarity of the filler, improving the compatibility between the filler and the sugarcane-based bio-polyethylene, making the filler uniformly dispersed in the polyethylene, and enabling the polyethylene to obtain uniform and stable mechanical strength and degradation effect.

[0055] 3. By comparing Examples 5-6 with Example 2, it can be found that the mechanical strength, degradation rate and antibacterial properties of the polyethylene prepared in Examples 5-6 are improved, which means that the Haematococcus pluvialis powder and Spirulina powder in the present application have more hydrophilic groups such as -OH, -C=O, and -COOH, which will be attacked by microorganisms in water, thereby giving the polyethylene a better hydrophilic effect, enabling microorganisms in water to attach to the surface of the material for erosion, and the degraded algae powder can form holes and grooves in the material, which can provide more holes and grooves for microorganisms, provide more adsorption sites for microorganisms, and accelerate the breaking of covalent bonds of the composite material, so as to achieve the purpose of accelerating the degradation of polyethylene.

[0056] 4. By comparing Examples 7-8 with Example 2, it can be found that the mechanical strength, degradation rate and antibacterial performance of the polyethylene prepared in Examples 7-8 are all improved, which indicates that in this application, it is preferred to use Poria powder or tea extract as filler. Both Poria powder and tea extract have antibacterial components such as polyphenols, which can further improve the antibacterial effect of polyethylene and slow down the degradation rate of polyethylene by microorganisms. Tea extract, zinc oxide, iron oxide, graphite phase carbon nitride and nano silver ions are dispersed in DMSO solution in advance. Tannic acid in tea extract can form complexes with metal ions, further improving the bonding effect between filler and polyethylene, so that the filler can stabilize and improve the mechanical strength of polyethylene.

[0057] 5. By comparing Example 9 with Example 2, it can be found that the mechanical strength, degradation rate and antibacterial performance of the polyethylene prepared in Example 9 are all improved, which indicates that the orange peel powder in the present application contains a large number of active functional groups such as hydroxyl and carbonyl, which can be added to polyethylene to increase the crosslinking degree of polyethylene through functional group binding, that is, further improve the mechanical strength of polyethylene. Preferably, silicon dioxide is used as a filler to be added to polyethylene, and silicon dioxide can form a strong covalent bond with the polyethylene matrix, further improving the crosslinking effect of polyethylene to improve the mechanical strength of polyethylene.

[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A sugarcane-based bio-polyethylene degradable modified particle, characterized in that: Including the following materials by weight: 100 parts of sugarcane-based polyethylene; 10-30 parts of filler; 2-5 parts of lubricant; 0.5-2 parts of compatibilizer; 2-5 parts of plasticizer; The filler includes any one or more of zinc oxide, graphite carbon nitride, iron oxide and nano silver particles.

2. The sugarcane-based bio-polyethylene degradable modified particles according to claim 1, characterized in that: The filler is a filler modified by a modifier, and the modifier is selected from sodium poly(p-styrene sulfonate) or methacryloxypropyltrimethoxysilane.

3. The sugarcane-based bio-polyethylene degradable modified particles according to claim 1, characterized in that: The filler also includes Haematococcus pluvialis powder or Spirulina powder.

4. The sugarcane-based bio-polyethylene degradable modified particles according to claim 3, characterized in that: The Haematococcus pluvialis powder is Haematococcus pluvialis powder containing astaxanthin.

5. The sugarcane-based bio-polyethylene degradable modified particles according to claim 3, characterized in that: The filler also includes tuckahoe powder and tea extract.

6. The sugarcane-based bio-polyethylene degradable modified particles according to claim 5, characterized in that: The tea extract is prepared as follows: tea leaves and tea stems are crushed, immersed in ethanol, extracted at room temperature, filtered, solids are discarded, and concentrated by rotary evaporation to obtain the tea extract.

7. The sugarcane-based bio-polyethylene degradable modified particles according to claim 5, characterized in that: The tea extract is pre-dispersed in a DMSO solution with zinc oxide, iron oxide, graphite phase carbon nitride and nano silver ions.

8. The sugarcane-based bio-polyethylene degradable modified particles according to claim 5, characterized in that: The fillers also include orange peel powder and silicon dioxide.

9. The sugarcane-based bio-polyethylene degradable modified particles according to claim 1, characterized in that: The compatibilizer is selected from maleic anhydride grafted polyethylene with a grafting rate of 8%, the lubricant is selected from polyethylene wax or calcium stearate, and the plasticizer is glycerol.

10. The sugarcane-based bio-polyethylene degradable modified particles according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Raw material preparation: weigh sugarcane-based polyethylene, filler, compatibilizer, lubricant and plasticizer respectively according to the above weight parts; S2. Preparation of modified particles: The filler is crushed in advance to obtain filler powder, the filler powder is mixed with a lubricant, a bulking agent and a plasticizer in advance to obtain a mixture, and the mixture and sugarcane-based polyethylene are put into an extruder, and extruded and granulated to obtain modified particles.

Citation Information

Patent Citations

  • Fly-ash-supported crosslinked-starch-modified low-density-polyethylene degradation mulch film and preparation method thereof

    CN105017620A

  • Formula of biodegradable cosmetic plastic bottle

    CN111533982A

  • Degradable TPE composite material and preparation method thereof

    CN117004244A

  • Degradable cable composite material, preparation method thereof and cable

    CN117777584A

  • Vapor-phase antirust film and preparation method thereof

    CN117801481A

Cited By

  • Granular material for sugarcane-based biological polyethylene antibacterial packaging film and preparation method

    CN120988388A